Sustainable Candle Production from Waste Cooking Oil and Waste Lubricating Oil - Wardana, Dian; Ramadhan, Dwi Sapri; Fahmi, Jaman; Safitri, Wulan Dwi; Damanik, Wicha Rosari; Simamora, Astuty Evalina; Sigalingging, Olivia Gina Ananta; Manullang, Okto Panca; Rahmadyani, Zaskia; Zubir, Moondra; S, Abd Hakim (Universitas Negeri Medan, 2025)
This study investigates the potential utilization of waste cooking oil and used lubricant oil as raw materials for candle production. These waste materials, often regarded as environmental pollutants, contain fats and hydrocarbons that can be converted into value-added products. The manufacturing process involved filtration, heating, and the incorporation of additives such as paraffin wax to enhance quality and stability, followed by molding. The resulting candles demonstrated acceptable physical properties, including melting points and burning times comparable to standard requirements. However, noticeable differences in color and odor were observed when compared to commercial candles. Despite these limitations, the valorization of waste cooking oil and used lubricant oil presents an environmentally friendly and cost-effective alternative, contributing to the development of sustainable products. Further research is recommended to optimize the blending ratios and additive compositions in order to improve the overall performance of the candles